Manajemen Pakan dan Pemenuhan Nutrisi pada Anoa Gunung (Bubalus Quarlesi) di Citra Satwa Celebes - Hidayat, Bahrul; Amrullah, Syarif Hidayat; Aswar, Asrul (Anoa: Journal of Animal Husbandry, 2025)
Anoa (Bubalus sp.) is an endemic animal from Sulawesi whose sustainability is threatened. Animal feed in the form of green fodder is very important for the health of anoa, but its utilization is constrained by dry land. Feed is divided into natural feed that is available directly in nature and artificial feed processed from a mixture of natural ingredients. This study aims to observe the type of feed, feed management, providing nutrition, and daily behavior of anoa at the Citra Satwa Celebes Zoo, as part of an effort to conserve this ex-situ species. The method used is a qualitative descriptive method. Anoa are given a variety of feed, including para grass, elephant grass, kale and tofu dregs, to meet the needs of fiber, protein, vitamins, and minerals in captivity. Feed management is carried out twice a day; tofu dregs which are rich in protein are given in the morning, while green grass is given in the afternoon to support digestion. The results of observations show that the feed given has met the basic nutritional needs of anoa with a protein content of 8.5% and crude fiber of 28%. The daily activity pattern of anoa is biphasic, with the main activities being feeding, walking, and resting in the morning and evening. These findings suggest that proper feeding management can support the physical health and psychological well-being of anoa in captive environments, and contribute to the success of conservation programs for this species.